2018
DOI: 10.1371/journal.pone.0195391
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability and performance of a directly assisted oral HIV self-testing intervention in adolescents in rural Mozambique

Abstract: IntroductionWhereas progress in HIV testing and treatment has been made globally, the UNAIDS goal of “90 90 90” is still out of sight in rural northern Mozambique. New strategies that promote testing in hard to reach groups will aid Mozambique’s response to the HIV epidemic. HIV self-testing (HIVST) is recommended by the WHO as an additional approach to augment the HIV testing services available to adolescents. This study evaluates acceptability and performance of a directly assisted oral HIVST intervention fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
69
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(79 citation statements)
references
References 29 publications
7
69
0
1
Order By: Relevance
“…In our observation of 16 participants as part of the formative assessment before the distribution of the kits, common errors include not collecting sample correctly, not putting the swab into the bottle correctly, and not waiting enough time (20 minutes) before reading the result [data not shown]. In this current study, we found a fairly high rate of indeterminate or invalid results or uncertainty of result (4.4%), which is higher than what has been reported when subjects performed supervised oral HST after a demonstration of the test kit usage in a rural community in rural Mozambique (5/496 = 1.7%) . However, one of the first HIVST validation studies conducted in Kenya in 2013 reported a higher rate of invalid HIV results (37/239 = 15.5%) .…”
Section: Discussionmentioning
confidence: 99%
“…In our observation of 16 participants as part of the formative assessment before the distribution of the kits, common errors include not collecting sample correctly, not putting the swab into the bottle correctly, and not waiting enough time (20 minutes) before reading the result [data not shown]. In this current study, we found a fairly high rate of indeterminate or invalid results or uncertainty of result (4.4%), which is higher than what has been reported when subjects performed supervised oral HST after a demonstration of the test kit usage in a rural community in rural Mozambique (5/496 = 1.7%) . However, one of the first HIVST validation studies conducted in Kenya in 2013 reported a higher rate of invalid HIV results (37/239 = 15.5%) .…”
Section: Discussionmentioning
confidence: 99%
“…Direct (i.e. primary) distribution of HIVST in sub‐Saharan Africa has shown to successfully reach high testing rates among AYA across various testing modalities [23‐26]. However, to our knowledge, ADORE is among the first studies exploring secondary distribution of HIVST during home‐based HIV testing in AYA.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in sub-Saharan Africa have shown high acceptability, uptake and accurate use of HIV self-testing (HIVST) in men and women in populations such as adolescents [5][6][7][8], female sex workers and their partners [9,10], and partners of women seeking antenatal and postnatal care [10,11]. Compared to provider-initiated testing and counselling, facility-based HIVST has been shown to be highly acceptable among adolescents aged 15 to 24 years [8].…”
Section: Introductionmentioning
confidence: 99%
“…In the context of using PrEP, HIVST has been shown to be highly acceptable by mutually disclosed serodiscordant couples [12] and female sex workers who are interested in PrEP [13]. Nevertheless, most studies of HIVST have only evaluated HIVST for screening [7,10,12,[14][15][16][17][18] and to date, no study has evaluated the integration of facility-based HIVST in PrEP delivery and its use as a tool to optimize patient flow and visit efficiency.…”
Section: Introductionmentioning
confidence: 99%